2013
DOI: 10.4319/lo.2013.58.5.1790
|View full text |Cite
|
Sign up to set email alerts
|

Food web consequences of size‐based predation and vertical migration of an invertebrate predator (Leptodora kindtii)

Abstract: In an intensive study of the vertical and horizontal distribution of zooplankton in a eutrophic lake (Katepwa Lake), we found that only adult Leptodora kindtii (. 5 mm in body size) exhibited diel vertical migration (DVM), whereas juvenile Leptodora (, 5 mm) and other zooplankton species did not. Even though a longitudinal survey of five lakes (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) indicated that variation in Leptodora density was correlated with several indicators of habitat use (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 52 publications
(83 reference statements)
3
37
0
Order By: Relevance
“…Functional differences between them arise from their body shape and habitat, since Leptodora is more elongated and Polyphemus tends to prey also in the littoral zone (Fl€ ossner 1972). These taxa have specific roles in the food web, consuming smaller invertebrates for food and being food items for fish and larger zooplankton, for example copepods, and their occurrence in the community provides information on structure of the food web (Herzig 1995;Packard 2001;Vogt et al 2013). Dynamics of predatory cladocerans have been used previously in examining long-term functioning of aquatic food webs with respect to, for example, eutrophication ) and biomanipulation (Nyk€ anen et al 2010), where the abundance and size structure of zooplankters changed significantly during these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Functional differences between them arise from their body shape and habitat, since Leptodora is more elongated and Polyphemus tends to prey also in the littoral zone (Fl€ ossner 1972). These taxa have specific roles in the food web, consuming smaller invertebrates for food and being food items for fish and larger zooplankton, for example copepods, and their occurrence in the community provides information on structure of the food web (Herzig 1995;Packard 2001;Vogt et al 2013). Dynamics of predatory cladocerans have been used previously in examining long-term functioning of aquatic food webs with respect to, for example, eutrophication ) and biomanipulation (Nyk€ anen et al 2010), where the abundance and size structure of zooplankters changed significantly during these processes.…”
Section: Discussionmentioning
confidence: 99%
“…In Enonselkä, Secchi depth during the study was 2.5 m and the thickness of euphotic zone c. 5 m (Hertta database, ; Ketola et al, ). In a lake with a Secchi depth of 1.8 m, Vogt et al () reported a <2 m vertical migration amplitude of Leptodora . Chang and Hanazato () found <2 m vertical migration amplitudes for Leptodora in a eutrophic lake where Secchi depth varied between 0.5–3 m. At all study stations in Enonselkä, water depth exceeded 3 m, the average depth being 10.4 m. Thus, the nocturnal increase in the abundance of Leptodora at most of the stations in Enonselkä could not be explained by bottom‐dwelling behavior during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Most zooplankton samples are taken during daylight. This affects the accuracy of density and biomass estimates, as several studies have shown that daytime estimates on the abundance of large pelagic invertebrates differ from those taken at night (Grossnickle & Morgan, ; Vogt, Matthews, Cobb, Graham, & Leavitt, ; Voss & Mumm, ). The reasons for the day‐night differences are not always clear however.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations